2009
DOI: 10.1590/s1517-83822009000200032
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of origanum vulgare l. essential oil and acetic acid for controlling the growth of staphylococcus aureus in foods

Abstract: This study evaluated the occurrence of an enhancing inhibitory effect of the combined application of Origanum vulgare L. essential oil and acetic acid against Staphylococcus aureus by the determination of Fractional Inhibitory Concentration (FIC) index and kill-time assay in nutrient broth, meat broth and in a food model (meat pieces). Acetic acid showed MIC and MFC of 0.6 and 1.25 µL.mL -1 , respectively. For O. vulgare essential oil MIC and MBC were 1.25 and 2.5 µL.mL -1 , respectively. FIC indexes of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 42 publications
1
21
0
2
Order By: Relevance
“…At lower pH the essential oils are more hydrophobic and can more easily dissolve in lipids of bacterial cell membrane (Juven et al 1994). Several authors reported synergy or additive effect of OEO (or its main component carvacrol) and lactic, acetic or citric acid against foodborne pathogens (Dimitrijevic et al 2007;Zhou et al 2007;de Souza et al 2009;de Oliveira et al 2010). In our study the presence of lactic, acetic or citric acid at concentration of either 0.05% (Fig.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…At lower pH the essential oils are more hydrophobic and can more easily dissolve in lipids of bacterial cell membrane (Juven et al 1994). Several authors reported synergy or additive effect of OEO (or its main component carvacrol) and lactic, acetic or citric acid against foodborne pathogens (Dimitrijevic et al 2007;Zhou et al 2007;de Souza et al 2009;de Oliveira et al 2010). In our study the presence of lactic, acetic or citric acid at concentration of either 0.05% (Fig.…”
Section: Discussionmentioning
confidence: 53%
“…Although no synergy was detected between OEO and CA, the additive effect still enables to obtain the same antimicrobial effect as that of OEO or CA alone using lower concentrations of both of the substances simultaneously. The effective concentration can be very important for use in food since both CA and OEO have a distinctive odour and the efficiency of essential oils is generally lowered in foodstuffs such as meat, requiring higher concentrations that are often sensory unacceptable (de Souza et al 2009;de Oliveira et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The essential oils were assayed at concentrations ranging from 80 to 0.003 μL/mL. Essential oils solutions were prepared in nutrient broth (Himedia, India) using bacteriological agar (1.5 g/L) as stabilizing agent (Souza et al, 2009 Inocula used in antimicrobial assays were obtained from overnight cultures grown on nutrient agar slants at 35°C for L. monocytogenes and Y. enterocolitica, and at 28°C for A. hydrophilla and P. fluorescens. A loopfull of the culture was diluted in sterile saline solution (8.5 g/L) to have a final concentration of approximately 10 8 colony forming unit per mL (cfu/mL) adjusted according to the turbidity of 0.5 McFarland standard tube.…”
Section: Essential Oilsmentioning
confidence: 99%
“…Early studies showed that Origanum vulgare L. (oregano) and Rosmarinus officinalis L. (rosemary) essential oils possess interesting antimicrobial activity against spoilage and pathogenic food-related microorganisms (Oliveira, Stamford, Gomes Neto, & Souza, 2010;Souza, Barros, Conceição, Gomes Neto, & Costa, 2009). Early in vitro assays with essential oils showed they had promising antimicrobial properties, however when applied to food matrices amounts required to substantially inhibit the bacterial growth were often higher than would be organoleptically acceptable (Naveena, Muthukumar, Sen, Babji, & Murthy, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing interest in using EOs by the food industry as natural preservatives against food spoilageand food-borne pathogenic microbes, in order to meet consumer demands for avoiding synthetic components in food [2]. Previous reports suggest that the preservative effect of EOs in food often requires higher doses than observed in vitro [1,[3][4][5]. It is believed that foodstuffs with high protein and fat content can protect bacteria from the antibacterial effect of EOs and other natural antimicrobials [6][7][8].…”
Section: Introductionmentioning
confidence: 99%